Improvement of information on the conditions of children - McGranahan, Donald (UN Research Institute for Social Development GenevaCH, 1980)
Reviews the present status of information on the conditions of children in developing countries and points to major gaps and deficiencies in quantitative data. Examines costs and technical problems in the collection of the relevant information through household surveys and other methods. Suggests the need for a reconsideration of conventional approaches to collection of data on children and for experimentation on innovative methods.